Synthesis, and reverse screening of 6‐(3, 4, 5‐trimethoxyphenyl)pyrimidine‐5‐carbonitrile derivatives as anticancer agents: Part‐II. (23rd December 2021) - Nainwal, Lalit Mohan; Shaququzzaman, Mohammad; Akhter, Mymoona; Husain, Asif; Parvez, Suhel; Tasneem, Sharba; Iqubal, Ashif; Alam, Mohammad Mumtaz
Abstract: In continuation to our previous studies on cyanopyrimidine derivatives as anticancer agents, we further designed, synthesized, and evaluated new 3, 4, 5‐trimethoxy phenyl ring pendant sulfur‐containing cyanopyrimidine derivatives (4a–m ) with a particular lipophilic behavior. In this work, we have varied the chain length from isopropyl to isopentyl and evaluated their anticancer activities. To study the antiproliferative spectrum, in vitro evaluation was piloted against a panel of 60 cancer cell lines at the National Cancer Institute, United States. Compound 4g (NSC: D‐813664) displayed the most promising broad‐spectrum anticancer activity with high growth inhibition of various cell lines representing action against multiple cancers diseases. It showed percentage growth inhibition of 84.01 and 76.94 against SR leukemia and HCT‐116 colon cancer cell lines. Absorption, distribution, metabolism, excretion, and toxicity studies and reverse screening were also performed to identify the potential targets of designed molecules. It was concluded that 6‐(3, 4, 5‐trimethoxyphenyl) pyrimidine‐5‐carbonitrile derivatives exhibited its anticancer activity through different targets and hence could be further structurally modified and optimized to develop more potent multi‐targeting anticancer agents. Abstract :